Ocular Delivery of Bimatoprost-Loaded Solid Lipid Nanoparticles for Effective Management of Glaucoma - Sandeep Divate Satyanarayana; Amr Selim Abu Lila; Afrasim Moin; Ehssan H. Moglad; El-Sayed Khafagy; Hadil Faris Alotaibi; Ahmad J. Obaidullah; Rompicherla Narayana Charyulu (MDPI AG, 2023)
Glaucoma is a progressive optic neuropathy characterized by a rise in the intraocular pressure (IOP) leading to optic nerve damage. Bimatoprost is a prostaglandin analogue used to reduce the elevated IOP in patients with glaucoma. The currently available dosage forms for Bimatoprost suffer from relatively low ocular bioavailability. The objective of this study was to fabricate and optimize solid lipid nanoparticles (SLNs) containing Bimatoprost for ocular administration for the management of glaucoma. Bimatoprost-loaded SLNs were fabricated by solvent evaporation/ultrasonication technique. Glyceryl Monostearate (GMS) was adopted as solid lipid and poloxamer 407 as surfactant. Optimization of SLNs was conducted by central composite design. The optimized formulation was assessed for average particle size, entrapment efficiency (%), zeta potential, surface morphology, drug release study, sterility test, isotonicity test, Hen's egg test-chorioallantoic membrane (HET-CAM) test and histopathology studies. The optimized Bimatoprost-loaded SLNs formulation had an average size of 183.3 ± 13.3 nm, zeta potential of −9.96 ± 1.2 mV, and encapsulation efficiency percentage of 71.8 ± 1.1%. Transmission electron microscopy (TEM) study revealed the nearly smooth surface of formulated particles with a nano-scale size range. In addition, SLNs significantly sustained Bimatoprost release for up to 12 h, compared to free drug (p < 005). Most importantly, HET-CAM test nullified the irritancy of the formulation was verified its tolerability upon ocular use, as manifested by a significant reduction in mean irritation score, compared to positive control (1% sodium dodecyl sulfate; p < 0.001). Histopathology study inferred the absence of any signs of cornea tissue damage upon treatment with Bimatoprost optimized formulation. Collectively, it was concluded that SLNs might represent a viable vehicle for enhancing the corneal permeation and ocular bioavailability of Bimatoprost for the management of glaucoma.